INFOGRAPHIC IN DISCOVERY LEARNING: CAN IT IMPROVE THE LEARNING PROCESS AND NUMERICAL LITERACY FOR STUDENTS? - Wilda Wilda; Wawan Krismanto; Ila Israwaty (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This article reviews a classroom action in the form of the application of the discovery learning model assisted by infographic teaching materials to improve the learning processes and numeracy literacy skills of fourth-grade students at SD Negeri 6 Benteng Sidrap Regency of South Sulawesi in Indonesia. The approach is qualitative with the type of classroom action research (CAR). The research was conducted in two cycles on two-dimensional geometric shapes material. Each cycle was conducted in two learning meetings. The research results indicate that after implementing the action, the learning process reveals various changes, such as the focus, activity and involvement, and learning interactions. This change led to the improvement of students' numeracy literacy skills. The action in cycle I indicate that out of 20 students, five students (25%) were in the high-ability category and seven students (35%) were in the medium-ability category. Eight students (40%) were still in the low-ability category. In terms of the action in cycle II, there were 14 students (70%) who were in the high ability category, three students (15%) were in the medium ability category, and three students (15%) were still in the low ability category. The conclusion is that applying the Discovery Learning model supported by infographic teaching materials can improve fourth-grade students' learning process and numeracy literacy skills at SD Negeri 6 Benteng of Sidrap Regency in South Sulawesi.Â Â